Copyright Exceptions for Teaching and Research Purposes: A Comparative Study Between Palestine and Malaysia - Qtait, Mohammed Mahmoud; Awang, Mohammed Nizam; A. Shukor, Haliza; Ghulam Khan, Intan Nadia (UUM Press, 2023)
Copyright exceptions for teaching and research purposes have turned into a significant issue for achieving a balance between the copyright owner and copyright users. The regulation of this issue is reflected in the Copyright Acts 1911 and 1987 for Palestine and Malaysia, respectively. The Palestine Copyright Act 1911 dismisses teaching and research copyright exceptions in detail and has not been amended since 1911; signifying a huge setback in regulating this issue and the pressing need to improvise the Act in order to achieve a balance between the copyright owner and copyright users. The present study has looked into the teaching and research exceptions detailed in the Palestine Copyright Act 1911 with the aim of suggesting improvements in the Act. The comparative research approach was used, along with a functional method. The findings revealed that the Malaysia Copyright Act 1987 offers several provisions in regulating the teaching and research exceptions based on a fair dealing rule, while the Palestine Copyright Act 1911 lacked provisions in regulating these exceptions despite its fair dealing principle. This points to the need for improvements in the Palestine Copyright Act 1911.